Optimizing therapy for cardiovascular diseases: proven organ-protective and preventive effects of pitavastatin and lercanidipine: A review - Marina G. Bubnova (КардиоСоматика, 2022)
The article aims to systematize the available data on the current use of statins and calcium channel antagonists (CA) for cardiovascular disorders therapy and to analyze the results of clinical trials focused on pitavastatin and lercanidipine. The article addresses the safety and tolerability of statins and CA and their use in the treatment of various conditions. Pharmacological features, preventive and organ-protective effects of pitavastatin and lercanidipine are described. The publications from the MEDLINE/PubMed, Scopus, Cochrane Library, eLIBRARY, and Google Scholar databases over the past 25 years were analyzed. The evidence presented in the article warrants the more extensive use of statins and CA in the treatment of patients with cardiovascular disease.